THE APPLICATION OF PROJECT-BASED LEARNING TO ENHANCE CREATIVITY AND COLLABORATIVE SKILLS AMONG PRIMARY SCHOOL PUPILS IN THE ERA OF THE MERDEKA CURRICULUM - Busnawir; Aslan Aslan (Indonesian Journal of Education (INJOE), 2026)
This study aims to analyse the implementation of the Project-Based Learning (PjBL) model in enhancing the creativity and collaborative skills of primary school pupils in the era of the Merdeka Curriculum. It employs a literature review (library research) using a descriptive qualitative approach. The findings indicate that PjBL, when integrated with the principles of the Merdeka Curriculum—through flexible time allocation, differentiated learning, and the Pancasila Student Profile Strengthening Project (P5)—significantly enhances pupils’ creativity across the indicators of fluency, flexibility, originality, and elaboration of ideas. Furthermore, PjBL is also effective in developing collaborative skills through mechanisms of positive interdependence, individual accountability, and structured group reflection. Empirical evidence from various studies reports a 35–45% increase in students’ creativity and collaboration scores following the implementation of PjBL over 8–12 weeks. Although challenges such as time constraints, variations in student ability, and the complexity of assessment remain, strategic solutions including continuous teacher training, the provision of adaptive project modules, and the use of assessment technology can overcome these obstacles. It is concluded that PjBL is a relevant and evidence-based pedagogical approach for fostering the Pancasila Student Profile—creative, collaborative, and ready to face the challenges of the 21st century.